Святогор та Марко Святогорець - Лома, А. (Народна творчість та етнологія, 2012)
Inherently probable, the existence of oral poetry among the Slavs in their proto-home before the Migration Age is inferred from a number of etymological matches of whole poetic formulas between South Slavic and Russian epic traditions, which suggests that the similarities of their figures and plots may be explained, too, as a common inheritance rather than due to independent or later developments, and where both form and content are comparable, the research results in reconstructing fragments of Common Slavic heroic and mythological poetry. The present paper aims at recovering such a fragment.